2017
DOI: 10.1021/acs.orglett.7b03448
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenative [2 + 3]-Cyclization of Glycine Esters with Aziridines Leading to Imidazolidines

Abstract: Oxidative dehydrogenative [2 + 3]-cyclization of glycine derivatives with N-sulfonylaziridines is described. A series of complex imidazolidines were produced under mild and simple reaction conditions. A mechanism involving an unusual acid-promoted auto-oxidation is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Our investigation began with optimization of the reaction of benzyl 2‐benzylhydrazinecarboxylate 1a with 2‐phenyl‐1‐tosyl‐ aziridine 2a (Scheme a). Under the similar reaction conditions of the ref , a product B was isolated. After overall screening, we found that the optimized reaction conditions for the coupling of two substrates include 10 mol% of copper acetate as the dehydrogenation catalyst under aerobic conditions, 20 mol% of boron trifluoride diethyl etherate as the nucleophilic ring opening catalyst, and dichloromethane as solvent under room temperature.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Our investigation began with optimization of the reaction of benzyl 2‐benzylhydrazinecarboxylate 1a with 2‐phenyl‐1‐tosyl‐ aziridine 2a (Scheme a). Under the similar reaction conditions of the ref , a product B was isolated. After overall screening, we found that the optimized reaction conditions for the coupling of two substrates include 10 mol% of copper acetate as the dehydrogenation catalyst under aerobic conditions, 20 mol% of boron trifluoride diethyl etherate as the nucleophilic ring opening catalyst, and dichloromethane as solvent under room temperature.…”
Section: Resultsmentioning
confidence: 91%
“…Very recently, our group achieved an oxidative dehydrogenative [2+3]‐cyclization of secondary amines with N ‐sulfonylaziridines to deliver substituted imidazolidines . We questioned if the substrates secondary amines were replaced with secondary hydrazines, as shown in Scheme , the method has the potential to produce triazine derivatives through [3+3] manner or N ‐amino imidazolidine derivatives through [2+3] manner.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…However, there are few data on the synthesis of analogous structures. [25][26][27][28] Acid 1 was synthesized by three methods. In the first method (Method A), glyoxylic acid ethyl ester (2) was condensed with potassium ethylene-1,2-disulfamate (3) at pH=3.4 and 45-50°С to furnish potassium 2-(ethoxycarbonyl)imidazolidine-1,3-5 disulfonate (4), which was then nitrated with concentrated HNO3 at between -35°С…”
Section: Scheme 2 13-dinitroimidazolidine-2-carboxylic Acidmentioning
confidence: 99%
“…In 2018, Huo and co-workers utilized aziridines as novel nitrogen sources in oxidative cycloaddition processes with glycine derivatives. 70 Aziridines constitute masked 1,3-dipoles prone to undergo formal [3+2] cyclizations with dipolarophiles. Accordingly, they described the synthesis of imidazolidine compounds through a novel oxidative dehydrogenative reaction of N-arylglycine esters and Nsulfonylaziridines (Scheme 27).…”
Section: Short Review Syn Thesismentioning
confidence: 99%